From Struggling to Maintaining Power: Cokroaminoto’s Maneuver in Political Crisis of Sarekat Islam in 1912-1921 - Ahmad Fajar (Islah: Journal of Islamic Literature and History, 2021)
Cokroaminoto is the eternal leader of Sarekat Islam. He succeeded in making Sarekat Islam into a big organization of Muslims in the Dutch East Indies. However, in his political career in Sarekat Islam, he experienced many internal conflicts with other Sarekat Islam’s member which were his opponent. In the conflict, there were conflict which formed several groups within Sarekat Islam. In this study, the researcher uses a historical research method including data collection, source criticism, data interpretation, and historical writing. This research aims to reveal the conflict of interest between Cokroaminoto and some Sarekat Islam’s figures. The results show Cokroaminoto’s role in Sarekat Islam. Furthermore, the internal conflict between Cokroaminoto and Goenawan-Samanhoedi to get member’s attention and influence is also explained. Cokroaminoto expelled communists within Sarekat Islamfor their political existence in the Dutch East Indies.